1999
DOI: 10.1007/s002130051091
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy of striatal D 2 -like dopamine receptors after treatment with the sigma ligand EMD 57445, a putative atypical antipsychotic

Abstract: Our results suggest that a possible antipsychotic activity of EMD 57445 in schizophrenia is not necessarily attributable to its affinity for sigma receptors, but could be simply due to the potent antidopaminergic effects of EMD 59983, its main metabolite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…EPS could not be detected in our sample of normal volunteers, either, although Farde's hypothesis would predict severe EPS al least at the higher doses administered. The observation that high D 2 receptor occupancy may not necessarily be strictly related to EPS or even clinical efficacy was already made with the sigma ligand EMD 57445 (Gründer et al 1999). In the case of aripiprazole, its partial dopamine agonism or dopamine autoreceptor agonism, respectively, may explain our unexpected findings.…”
Section: Discussionmentioning
confidence: 98%
“…EPS could not be detected in our sample of normal volunteers, either, although Farde's hypothesis would predict severe EPS al least at the higher doses administered. The observation that high D 2 receptor occupancy may not necessarily be strictly related to EPS or even clinical efficacy was already made with the sigma ligand EMD 57445 (Gründer et al 1999). In the case of aripiprazole, its partial dopamine agonism or dopamine autoreceptor agonism, respectively, may explain our unexpected findings.…”
Section: Discussionmentioning
confidence: 98%
“…Concern for metabolite confounders is based upon prior work showing that O ‐demethylation of some σ receptor ligands by cytochrome P450 enzymes can lead to centrally active metabolites with a different spectrum of activity. The atypical antipsychotic panamesine is highly selective for σ receptors in vitro, but is converted into a phenolic metabolite that occupies striatal dopamine D 2 ‐like receptors as observed by single photon emission computed tomography (SPECT) imaging studies in human beings (Gründer et al, ). To cite another instance, the major phenolic metabolite of ibogaine shows reduced affinity for σ 2 receptors, and 3‐ to 20‐fold higher affinity for the DAT and SERT, respectively (Baumann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors state that the mechanism of action of EMD 57445 remains unclear because the main metabolite of EMD 57445, EMD 59 983, has substantial affinity for the dopamine D 2 and D 3 receptors [1]. In a single photon emission computed tomography (IBZM-SPECT) study, Gründer et al [10] showed a high occupancy of striatal D 2 -like dopamine receptors similar to that induced by typical neuroleptics in five schizophrenic patients treated with EMD 57445. The D 2 -occupancy rate in the striatum correlated with the plasma levels of EMD 57445 and EMD 59 983.…”
Section: Compoundmentioning
confidence: 93%